Investigating the effect of gamification on the interest of the students of the first secondary school, the third grade of Parvin Etsami elementary school's mathematics course (Scientific Journal of Research Studies in Future Computer Sciences, 2024)
Gamification is a new method created with the development of smartphones. In this research, the effect of gamification on the score and the time that students spent studying mathematics at home has been investigated. This research is practical in terms of its purpose. In terms of the method of collection and analysis, it is a description of survey type. In this research, the Mann-Whitney mean test was used to test the hypotheses. The sample of the research was 24 students of elementary school, third grade, of Parvin Ettami School. In order to meet the necessary conditions for testing the research hypothesis, the statistical sample was divided into two categories: the test group and the control group. Based on this, 12 students were in the test group and 12 were in the control group. Therefore, the designed application was only given to the test group to evaluate the impact of using this application on students' learning compared to the control group. According to the results, the use of gamification has had a positive effect on improving the grade of the students under study and the amount of time they spent studying at home. Therefore, it is suggested to use this method to teach and learn lessons, especially in the secondary level, where students are more entertained by playing games.